EVALUASI PASKA HUNI ASPEK PERILAKU DI KANTOR KECAMATAN MANTRIJERON KOTA YOGYAKARTA - Triatmodjo, Suastiwi (Institut Seni Indonesia Yogyakarta, 2008)
Right now the District Office is a governmental office that has an increasing importantrole in giving services and generating regional income To develop its service perfomance theDistrict Office has an intention to rearrange the interior design of the office building therefore they need to do post occupancy evaluation research This research concentrates on thebehavioural aspect The basic assumption of this reasearch is that the built environment is designed to fulfill the needs of human life as effectively as possible whereas human effectiveness in any activity is greatly influenced by social and psychological factors Thereby the success of an interior design does not only depend on technical functional and aestheticconsiderations but also on behavioural consideration This research has found typical behaviours which need to be considereded carefully in the planning and design of the DistrictOffice interior in the futureKey words : district office interior behaviour